2022
DOI: 10.1177/03635465211067806
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Quantitative Measurement of Medial Clear Space for Deltoid Injury of the Ankle: A Cadaveric Comparative Study With Stress Radiography

Abstract: Background: The deltoid ligament (DL) is an important stabilizer of the ankle. DL injury of varying severity can occur alone or with syndesmotic injury and fibular fracture. Limited diagnostic tools are available to assess DL injury quantitatively. Purpose: To establish an arthroscopic quantitative assessment of DL injury and to compare its performance with that of external rotation stress (ERS) and gravity stress (GS) radiography. Study Design: Controlled laboratory study. Methods: In total, 24 cadaveric lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…In line with the current study, Chiang et al [15] documented by arthroscopic quantitative analysis of medial clean space for deltoid damage of the ankle revealed that medial discomfort was related to DL injury and ankle instability. In this study, there was an insignificant correlation between MCS and deltoid ligament injury (PTTL, ATTL, TCL), syndesmotic ligaments injury (AITFL, PITFL, IOL), and lateral collateral ligament (Table 4) (Table 5).…”
Section: Discussionsupporting
confidence: 90%
“…In line with the current study, Chiang et al [15] documented by arthroscopic quantitative analysis of medial clean space for deltoid damage of the ankle revealed that medial discomfort was related to DL injury and ankle instability. In this study, there was an insignificant correlation between MCS and deltoid ligament injury (PTTL, ATTL, TCL), syndesmotic ligaments injury (AITFL, PITFL, IOL), and lateral collateral ligament (Table 4) (Table 5).…”
Section: Discussionsupporting
confidence: 90%
“…Some surgeons defined chronic medial ligament abnormality or injury as the drive‐through test in the medial mortise [9]. Chiang et al[8] reported that arthroscopic medial clear space measurement can differentiate intact DL (≤ 2.5 mm), partial DL injury (between 2.5 and 3.5 mm) and complete DL injury (≥ 3.5 mm) without using any stress. In the present study, we also used a 4‐mm arthroscope probe in the medial mortise to check the medal clear space.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Ankle arthroscopy is useful for assuring appropriate reduction of the fractures, assessment of the integrity of the deltoid ligament and syndesmosis, detection and treatment of subtle residual instability, guidance of anatomical reduction of the syndesmosis, determining interposition when the MCS remains wide after proper reduction, removal of loose bodies and treatment of osteochondral lesions. 2 , 6 , 10 , 15 , 16 , 17 …”
mentioning
confidence: 99%